Numerical Modeling of Settlement Behavior on Soft Soil Improved with Plastic Bottles - Abdul Razak, Nur Hadirah Afiqah; Yusof, Mohd Fairus (Recent Trends in Civil Engineering and Built Environment, 2024)
Used plastic bottles are frequently found among the waste that might pollute the environment. Because of their low density, these plastic bottles could be used to replace problematic soils that have a higher density than plastic bottles. As a result, this study was carried out to assess the use of plastic bottles in terms of soil bearing capacity and soft soil settlement. Plastic bottles with a volume of 500 ml were subjected to physical properties such as density and compression tests in order to determine the Young's Modulus. Two models were created with PLAXIS 2D software to compare soil improvement behaviour without plastic bottles with soil improvement with plastic bottles. This model was created using the axisymmetry model. The results demonstrate that the soft soil model with the plastic bottle lining has a better bearing capacity than the soil model without the plastic bottles. In terms of settlement behaviour, it also demonstrates that using plastic bottles can lower settlement, however, the difference is not statistically significant.